USE OF NON-OXIDIZING POLYMERIC REAGENT FOR TREATMENT OF WASTEWATER AND CREATION OF TURNAROUND WATER SUPPLY SYSTEM OF FACTORY - Нижник, Т. Ю. (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2010)
Results of use of polymeric non-oxidizing reagent (“Aquaton”: poly-(hexamethylene diamine, guanidinium hydrochloride) – EU; polyhexamethylene guanidine hydrochloride – RU) for treatment of wastewater and creation of factory turnaround water supply system were shown. It was shown that use of reagent “Aquaton” allows to achieve satisfying degree of water treatment and prevent microbial growth in turnaround system and sediments.